2020
DOI: 10.2217/bmm-2020-0274
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Immune-Inflammation Index Is A Novel Marker to Predict Functionally Significant Coronary Artery Stenosis

Abstract: Aim: The study aimed to investigate and compare the predictive capacity of a systemic immune-inflammation index (SII), neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) to determine a hemodynamically significant coronary artery stenosis assessed by fractional flow reserve (FFR). Patients & methods: A total of 207 chronic coronary syndrome patients with FFR measurement were enrolled in the study. NLR, PLR and SII levels were calculated. Results: The cut-off value of the SII (620) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
96
2
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 91 publications
(102 citation statements)
references
References 24 publications
1
96
2
3
Order By: Relevance
“…SII was found to be better than NLR and PLR as a prognostic marker in esophageal squamous cell carcinoma patients 23,24 . Likewise, we recently found that SII predicts hemodynamically significant CAD better than NLR and PLR 16 . Due to pathophysiological similarities between CAD and calcific AS described above, we hypothesized that SII levels may be increased and predict severe AS, and we found that SII levels both as a continuous and categorical variable independently predict calcific severe AS.…”
Section: Discussionmentioning
confidence: 57%
“…SII was found to be better than NLR and PLR as a prognostic marker in esophageal squamous cell carcinoma patients 23,24 . Likewise, we recently found that SII predicts hemodynamically significant CAD better than NLR and PLR 16 . Due to pathophysiological similarities between CAD and calcific AS described above, we hypothesized that SII levels may be increased and predict severe AS, and we found that SII levels both as a continuous and categorical variable independently predict calcific severe AS.…”
Section: Discussionmentioning
confidence: 57%
“…The systemic immune-inflammatory (SII) index is an integrated marker of systemic inflammation and it results from a combination of NLR and PLR. The SII index has been already extensively assessed as a marker of prognosis and mortality of patients with solid tumors or coronary artery disease [ 41 , 42 , 43 ]. Until now, very limited data is available concerning the relationship between SII index and psychiatric disorders.…”
Section: Introductionmentioning
confidence: 99%
“…[15] Post hoc analysis variable de nitions For this post hoc analysis, the in ammatory indexes were determined based on values of monocytes (M), neutrophils (N), lymphocytes (L), and/or platelets (P) in patients received surgical ablation at indicated data: SII de ned as P×N/L, NLR de ned as N/L, platelet-lymphocyte ratio (PLR) de ned as P/L, lymphocyte to monocyte ratio (LMR) de ned as L/M, monocytes-NLR (MNLR) de ned as M×N/L, monocytes-PLR (MPLR) de ned as M×P/L . [14,16,17]…”
Section: Patients' Selectionmentioning
confidence: 99%
“…[13] Systemic immune-in ammation index (SII) is a novel marker that brings together these three in ammatory peripheral cell counts and predict functionally signi cant coronary artery stenosis. [14] In this study, we investigated the association of perioperative systemic in ammation index, and changes during treatment, with outcomes in AF patients treated with CryoMaze concomitant with mitral valve surgery.…”
Section: Introductionmentioning
confidence: 99%